Hyperscanning: A Valid Method to Study Neural Inter-brain Underpinnings of Social Interaction - Czeszumski, Artur; Eustergerling, Sara; Lang, Anne; Menrath, David; Gerstenberger, Michael; Schuberth, Susanne; Schreiber, Felix; Rendon, Zadkiel Zuluaga; König, Peter (Frontiers in Human Neuroscience, 2020)
Social interactions are a crucial part of human life. Understanding the neural underpinnings of social interactions is a challenging task that the hyperscanning method is trying to tackle in the last two decades. Here, we review the existing literature and evaluate the current state of the hyperscanning method. We review the type of methods (fMRI, M/EEG, fNIRS) that are used to measure brain activity from more than one participant simultaneously and their pros and cons for hyperscanning. Further, we discuss different types of analyses that are used to estimate between brain networks and synchronization. Lastly, we present results of hypercanning studies in the context of different cognitive functions and their relations to social interactions. All in all, we aim to comprehensively present methods, analyses, and results of the last twenty years of hyperscanning research.